Nadumieralność mężczyzn w Polsce - analiza taksonomiczna - Gazińska, Mirosława (Excess Male Mortality in Poland - Taxonomic Analysis, 2007)
In article presents some information about excess male mortality in Poland. Excess male mortality is a surplus of the intensity of males' death over the females' death and it is natural occurrence. The author has shown the similarity of general and partial excess male mortality ratio by means of distance measures (City-block, Euclidean, and Chebychev distance) in two spatial schemes:- in years 1999-2004 according to place of residence (urban-rural) general and age groups,- in 2004 year according to regions of Poland general and age groups.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 219-227